Chloroplast Degradation: Multiple Routes Into the Vacuole - Zhuang, Xiaohong; Jiang, Liwen (Frontiers in Plant Science, 2019)
Chloroplasts provide energy for all plants by producing sugar during photosynthesis. To adapt to various environmental and developmental cues, plants have developed specific strategies to control chloroplast homeostasis in plant cells, including chloroplast degradation during leaf senescence and the transition of chloroplasts into other types of plastids during the day-night cycle. In recent years, autophagy has emerged as an essential mechanism for selective degradation of chloroplast materials (also known as chlorophagy) into the vacuole. Different types of membrane structures have been shown to be involved in the delivery of distinct chloroplast contents. However, the underlying mechanisms for the formation of these chlorophagy-related structures and the selectivity of chloroplast proteins remain poorly understood. Here we provide a current overview on chlorophagy and discuss the possible chloroplast receptors and upstream signals in this process.